The Interaction of the Noun and the Verb in Modern Russian Language - VISOCKAYA, IRINA (Bulletin of Yerevan University H: Russian Philology, 2021)
The author discusses different types of syncretic phenomena arising from the interaction of language units on the morphemic level of creation and transposition. Between the differentiated noun and the verb on the transitivity scale can be selected syncretic: peripheral phenomena (verbal nouns and the infinitive) and intermediate (forms of instantly-arbitrary action). The possibility of occasional substantival verb forms is defined, metatextual, individual-author and substantivation of the nomination are selected. The work is performed within the framework of structural-semantic field of modern Russian linguistics. The research material mainly was based on the artworks of classical and modern Russian literature.
Keywords: structural-semantic field, interaction between parts of speech, transition, syncretism, substantivization